Production of anhydrous hydrogen fluoride from fluorosilicic acid: a review - Yang, Huachun; Li, Shijiang; Yu, Hehua; Liu, Haixia; Sun, Kai; Chen, Xiaolan (Frontiers in Chemistry, 2024)
Anhydrous hydrogen fluoride (AHF), a critical raw material for industries such as aluminum, pharmaceuticals, and petroleum, has traditionally been sourced from fluorite—a non-renewable mineral. The unsustainable reliance on fluorite has catalyzed the search for alternative AHF production methods. A promising substitute is fluorosilicic acid (FSA), a byproduct of the phosphate fertilizer industry previously deemed waste. Transforming fluorosilicic acid into AHF not only yields a valuable resource but also addresses the environmental and economic challenges associated with waste management. The innovative practice of producing AHF from fluorosilicic acid signals a shift towards sustainable chemical production by capitalizing on waste, potentially diminishing reliance on fluorite and reducing the industry’s environmental impact. This review thoroughly dissects the AHF synthesis process from fluorosilicic acid. Despite the acknowledged importance of fluorinated compounds in numerous industrial applications, research on their synthesis from fluorosilicic acid is limited and fragmented. This review seeks to amalgamate this scattered information by closely scrutinizing diverse industrial processing methods. Additionally, it explores the current and future landscape, economic feasibility, and strategies to navigate the obstacles inherent in synthesizing AHF from fluorosilicic acid. It also assesses the environmental impact of these methods, thereby contributing to the dialogue in this emerging field. The primary aim of this manuscript is to foster further research and promote the industrial uptake of this sustainable process. Highlighting the challenges and proposing potential improvements, the review supports the responsible reuse of waste and advocates for advancements in industrial practices.